Hybrid Lectures with Problem-Based Learning to Improve Learning Outcomes - Dwi Nurma Heitasari; Bambang Sugito; Ika Gita Lestari (Proceeding International Conference on Religion, Science and Education, 2023)
Universities are faced with the great challenge of managing input from passive students into outputs ready to solve problems in the industry. One of the things universities can do to answer these challenges is to design and implement learning strategies that can turn surface learning into deep learning, from passive learning to active learning. One of the learning strategies that can be used to prepare students to become professional graduates is problem-based learning. This study aims to analyze, evaluate, and optimize the implementation of problem-based learning in practicum lectures, with case studies in the Practicum of Procurement System, Logistics of Oil and Gas Study Program, Polytechnic of Energy and Mineral Akamigas. The research design used experimental research in hybrid lectures and two analyses. The first analysis is to test the initial ability differences between the experimental group and the control group. The second analysis is to test the proposed hypothesis. In addition, psychomotor influences were also analyzed using Peer Assessment. The results showed that the problem-based learning model could improve students’ learning outcomes. The classes given problem-based learning have higher cognitive, affective, and psychomotor aspects of students compared to conventional ones.